Malate dehydrogenase activity in human seminal plasma and spermatozoa homogenates - Hulya Leventerler; Safiye Taga; Ibrahim Ferhat Urunsak; Ismail Atilla Aridogan; Suna Solmaz; Mehmet Turan Cetin; Nurten Dikmen (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Purpose: Malate Dehydrogenase is an important enzyme of the Krebs cycle, most cells require this enzyme for their metabolic activity. We evaluated the Malate Dehydrogenase (NAD/NADP) activity in human seminal plasma and sperm homogenates in normozoospermic, fertile and infertile males. Also glucose and fructose concentrations were determined in the seminal plasma samples. Material and Methods: Malate Dehydrogenase (NAD/NADP) activity in human seminal plasma and sperm homogenates of normozoospermic and infertile males was determined by spectrophotometric method. Semen analysis was considered according to the WHO Criteria. Results: Malat Dehydrogenase-NAD value in seminal plasma (the mean ± SD, mU/ml) of asthenoteratospermic (40.0±25.7) and azospermic (38.0±43.6) groups were significantly lower than normozoospermic, (93.9±52.1) males. Malat Dehydrogenase-NAD value in sperm homogenates (the mean ± SD, mU/ 20x106 sperm) of teratospermic group (136.8±61.8) was significantly higher compared to the normozoospermic (87.3±26.5) males. Glucose concentration (mg/dl) in asthenoteratospermic (4.0±1.4) and azospermic (15.4±6.4) groups were significantly higher than fertile (2.0±2.1) males. Also fructose concentration (mg/dl) in asthenoteratospermic (706.6±143.3) and azospermic (338.1±228.2) groups were significantly high compared to the normozoospermic (184.7±124.8) group. Conclusion: Sperm may be some part of the source of Malat Dehydrogenase activity in semen. Malat Dehydrogenase activity in seminal plasma has an important role on energy metabolism of sperm. Intermediate substrates of Krebs cycle might have been produced under the control of Malat Dehydrogenase and these substrates may be important for sperm motility and male infertility. [Cukurova Med J 2013; 38(4.000): 648-658]